Monster trucks and other giant machines on wheels - Bushey, Jerry (Minneapolis : Carolrhoda, 1985)
Text and photographs introduce various large machines with wheels, including a snowblower, a trash truck, a ready-mix truck, and a platform loader.
School Library Journal.
4.4
K-3
Keywords: Motor vehicles -- Juvenile literature; Machinery; Motor vehicles; Machinery; Trucks; Motor vehicles; Machinery; Monster trucks; Motor vehicles